A study on preferences that affecting voting behaviour In N17 Stakan / Norazrin Amin and Richard Jihun - Amin, Norazrin; Jihun, Richard (2016)
Politics is defined as process of making decisions applying to all members of each group. More narrowly, it refers to achieving and exercising positions of governance organized control over a human community, particularly a state. Furthermore, politics is the study or practice of the distribution of power and resources within a given community (a usually hierarchically organized population) as well as the interrelationship(s) between communities. It is very often said that politics is about power. A political system is a framework which defines acceptable political methods within a given society. According to Ahem 2015, he made a legislative issue in his own picture - moderate, consensual, comprehensive, client list, populist. Ahem utilized his dumbfounding nature for what voters needed, and what they would endure, to accomplish political force. In any case, past keeping individuals cheerful, he never explained a reason for that power. Politics has an expressive field and elections are the main architects ofthese fields.